Analysis of Student Satisfaction and Loyalty through Educational Service Quality and Lecturer Performance in Islamic University - Suriadi, Hari; Putri, Nora Eka; Wahyuni, Yulia Septi (International Journal of Islamic Studies Higher Education, 2025)
The issue of student loyalty to higher education institutions is an important concern in education management, especially because student loyalty can reflect the success of educational services and lecturer performance. This study aims to analyze the effect of educational service quality and lecturer performance on student satisfaction, as well as its impact on student loyalty in one of the Islamic universities in Indonesia. The research method uses a quantitative approach with Structural Equation Modeling analysis operated through the Analysis Moment of Structural version 28 application. The research sample consists of 300 randomly selected students. The results showed that the quality of educational services and lecturer performance had a positive and significant effect on student satisfaction, with estimated coefficients of 0.489 and 0.391 (p < 0.05), respectively. Student satisfaction also had the greatest influence on student loyalty (estimated coefficient of 0.6511; p < 0.05) and proved to be a significant mediating variable in the relationship between educational service quality and lecturer performance on student loyalty. The research model was declared fit with the data based on various fit indices such as The Minimum Sample Discrepancy Function divided by Degree of Freedom (1.512), Root Mean Square Error of Approximation (0.039), and Comparative Fit Index (0.961). The conclusion of this study shows that superior educational service quality and good lecturer performance can increase student satisfaction, which in turn contributes significantly to student loyalty. The findings provide practical implications for higher education institutions to focus on improving educational services and professional development of lecturers to create positive experiences for students.